Structural and Nonstructural Genes Contribute to the Genetic Diversity of RNA Viruses - Natalie D. Collins (American Society for Microbiology, 2018)
ABSTRACT One paradigm to explain the complexity of viral RNA populations is that the low fidelity of the RNA-dependent RNA polymerase (RdRp) drives high mutation rates and consequently genetic diversity. Like most RNA viruses, wild-type yellow fever virus (YFV) replication is error-prone due to the lack of proofreading by the virus-encoded RdRp. However, there is evidence that replication of the live attenuated YF vaccine virus 17D, derived from wild-type strain Asibi, is less error-prone than wild-type RNA viruses. Recent studies comparing the genetic diversity of wild-type Asibi and 17D vaccine virus found that wild-type Asibi has the typical heterogeneous population of an RNA virus, while there is limited intra- and interpopulation variability of 17D vaccine virus. Utilizing chimeric and mutant infectious clone-derived viruses, we show that high and low genetic diversity profiles of wild-type Asibi virus and vaccine virus 17D, respectively, are multigenic. Introduction of either structural (pre-membrane and envelope) genes or NS2B or NS4B substitutions into the Asibi and 17D backbone resulted in altered variant population, nucleotide diversity, and mutation frequency compared to the parental viruses. Additionally, changes in genetic diversity of the chimeric and mutant viruses correlated with the phenotype of multiplication kinetics in human alveolar A549 cells. Overall, the paradigm that only the error-prone RdRp controls genetic diversity needs to be expanded to address the role of other genes in genetic diversity, and we hypothesize that it is the replication complex as a whole and not the RdRp alone that controls genetic diversity. IMPORTANCE With the advent of advanced sequencing technology, studies of RNA viruses have shown that genetic diversity can contribute to both attenuation and virulence and the paradigm is that this is controlled by the error-prone RNA-dependent RNA polymerase (RdRp). Since wild-type yellow fever virus (YFV) strain Asibi has genetic diversity typical of a wild-type RNA virus, while 17D virus vaccine has limited diversity, it provides a unique opportunity to investigate RNA population theory in the context of a well-characterized live attenuated vaccine. Utilizing infectious clone-derived viruses, we show that genetic diversity of RNA viruses is complex and that multiple genes, including structural genes and NS2B and NS4B genes also contribute to genetic diversity. We suggest that the replication complex as a whole, rather than only RdRp, drives genetic diversity, at least for YFV.